2017
DOI: 10.1016/j.bjpt.2017.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and treatment of movement system impairment syndromes

Abstract: HighlightsImpaired movements and alignments may be associated with musculoskeletal conditions.Signs of impaired alignments and movements may be seen before there are symptoms.Treatment is based on using the findings of making the MSI diagnosis to correct the performance of daily activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
860
2
107

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 572 publications
(978 citation statements)
references
References 94 publications
(159 reference statements)
9
860
2
107
Order By: Relevance
“…Individuals with shoulder impingement syndrome were found to have decreased muscle activity in infraspinatus and middle deltoid during scaption compared to controls (Reddy et al , 2000), while patients with symptomatic rotator cuff tear were found to have decreased activity for the deltoid muscle (Shinozaki, Sano, 2014). One of the goals of physiotherapy is to restore optimal muscle recruitment patterns about the shoulder joint (Sahrmann, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with shoulder impingement syndrome were found to have decreased muscle activity in infraspinatus and middle deltoid during scaption compared to controls (Reddy et al , 2000), while patients with symptomatic rotator cuff tear were found to have decreased activity for the deltoid muscle (Shinozaki, Sano, 2014). One of the goals of physiotherapy is to restore optimal muscle recruitment patterns about the shoulder joint (Sahrmann, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The non-significant differences of anthropometric characteristics of both male and female Individuals with Anterior and neutral balance types suggest that anterior placement of hip in reference to plumb line is not influenced by these characteristics. If so, this can be also assumed that in contrast to neutral balance strategy which is supposed to be in majority otherwise, prevalence of anterior balance strategy in healthy young adults might be related to weakness of tight muscles of hamstrings, gastrocnemius and hip flexors as a result of adaptive shortening [23][24][25]. Adaptive shortening is often considered with functional overuse.…”
Section: Discussionmentioning
confidence: 99%
“…This imbalance can reinforce demand over stronger muscles and minimize demand over weaker ones thus creating a vicious cycle. Based on possible imbalances, Sahrmann 12 has developed a system for the diagnostic classification of muscle impairment syndromes. Treatment approaches aim to reestablish the appropriate balance in muscle activation patterns.…”
Section: Motor Synergiesmentioning
confidence: 99%